The role of organizational justice in reducing corruption in sports organizations - Merniz, Oussama; Briki, Tahar (Journal of Human Sciences, 2021)
This study aims to highlight the role of organizational justice in curbing the phenomenon of corruption that is pervasive in the sports community, especially in sports institutions, its implications for the sports environment, and one of the most important findings of our study is that the application of organizational justice elements gives confidence to workers and loyalty to the institution and thus they move away from All negative practices.